The Implementation of the Current Common Agricultural Policy in Bulgaria – Opportunities for Development - Byanov, Ivan (Research Papers, 2025)
This publication focuses on the development of the Common Agricultural Policy, with the latest changes for the program period 2023 – 2027, as well as its implementation in Bulgaria. Analyzes some key variables showing the development of agricultural holdings in Bulgaria and the potential possible scenarios in the future. The author does not claim to be exhaustive due to the small volume of the publication and, on the other hand, the multidimensional connectivity of the CAP with the strategic sector “agriculture” and the cohesion links with other EU policies.